2022
DOI: 10.1182/bloodadvances.2021006418
|View full text |Cite|
|
Sign up to set email alerts
|

Optimal fludarabine lymphodepletion is associated with improved outcomes after CAR T-cell therapy

Abstract: Chimeric antigen receptor (CAR) T-cells provide a therapeutic option in hematologic malignancies. However, treatment failure after initial response approaches 50%. In allogeneic hematopoietic cell transplantation, optimal fludarabine exposure improves immune reconstitution, resulting in lower nonrelapse mortality and increased survival. We hypothesized that optimal fludarabine exposure in lymphodepleting chemotherapy prior to CAR T-cell therapy would improve outcomes. In a retrospective analysis of relapsed/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…The observed clinical effect of high fludarabine exposure on the outcome is in line with the effect described by a recent publication of Fabrizio et al, 22 where the AUC was retrospectively estimated using the population pharmacokinetic model published by Langenhorst et al. 17 They show that patients with an estimated fludarabine AUC <13.8 mg*h/L had a significantly higher risk of relapse or B-cell recovery compared with patients with an estimated fludarabine AUC ≥13.8 mg*h/L after CD19 CAR T-cell infusion.…”
Section: Discussionsupporting
confidence: 91%
“…The observed clinical effect of high fludarabine exposure on the outcome is in line with the effect described by a recent publication of Fabrizio et al, 22 where the AUC was retrospectively estimated using the population pharmacokinetic model published by Langenhorst et al. 17 They show that patients with an estimated fludarabine AUC <13.8 mg*h/L had a significantly higher risk of relapse or B-cell recovery compared with patients with an estimated fludarabine AUC ≥13.8 mg*h/L after CD19 CAR T-cell infusion.…”
Section: Discussionsupporting
confidence: 91%
“…20 It is interesting to note that a recent retrospective study with relapsed/refractory B-cell acute lymphoblastic leukemia patients undergoing CAR T-cell (tisagenlecleucel) infusion after cyclophosphamide/fludarabine lymphodepleting chemotherapy illustrated that fludarabine exposure was related to overall survival and risk of relapse. 35 In addition to lymphodepletion regiments, direct modification of the CAR T cells to decrease HvG risks such as β2M knockdown can be envisaged. However, we and others are investigating as a first step the suitability and safety of the technology to inhibit GvHD since it would not be possible to evaluate multiple elements in a single trial.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lymphoma patients who achieve CR developed a greater increase of serum IL-15 levels after Flu/Cy LD and a greater area under the curve (AUC) of CAR19 T cells up to day +14 after infusion ( 38 ). Recent studies found that optimizing Flu exposure may have a relevant impact in PFS and OS of B-ALL R/R patients after CART19 ( 39 , 40 ). Examination of cumulative Flu exposure suggest that an AUC ≥ 14 mg*h/L is associated with a lower proportion of CD19 + relapses, lower cumulative incidence of B-cell recovery after CART19, and higher CAR19 T-cell expansion ( 39 ).…”
Section: Clinical Outcome After Cart19 Therapy Is Influenced By Patie...mentioning
confidence: 99%
“…In agreement with these data, another study in B-ALL found that a suboptimal Flu exposure (defined as AUC ≤ 13.8 mg*h/L) was associated with increased risk of relapse and loss of B-cell aplasia. Furthermore, Flu exposure was noted to affect OS in patients with high pre-infusion TB ( 40 ). These data indicate that adjustment of Flu dose may have a relevant impact on CART19 efficacy in patients with B-ALL, which should be prospectively studied in patients with DLBCL.…”
Section: Clinical Outcome After Cart19 Therapy Is Influenced By Patie...mentioning
confidence: 99%